SYNTHESIS AND CHARACTERIZATION OF NEW POLYMERIC COATINGS FROM ANTHOCYANIN DYE AND STUDY BIOLOGICAL ACTIVITY - Mayson Thafir Hadi; Zainab A. Jabarah; Sana H. Awad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to prepared new polymeric coverings reinforced by the naturally occurring pigment anthocyanins and investigate their biological efficacy when combined with certain drugs against specific kinds of microbe’s pathogens. FT-IR spectroscopy and mass spectrometry (MS) were used to identify the active groups of the anthocyanin pigment, which were situated the functional groups of anthocyanin in contrast to crystalline compounds, X-ray diffraction (XRD) examination also revealed the production of irregularly constituted compounds. Furthermore, all derivative compounds were had high inhibitory activity against the Gram-positive bacteria Staphylococcus aureus, as well as against the fungus Candida albicans in different concentrations.